Derivatives Market: A Survey - Alalmai, Somaiyah (International Journal of Economics and Financial Issues, 2023)
Our research paper surveys prior research on derivatives markets. We mainly review the literature investigating the impact of introducing derivatives markets on the underlying market and the overall economic development. Particularly, we summarize papers investigating the effects on the spot market liquidity, spot market volatility, and the price discovery process. We review the literature on several countries, but the survey paper appears to be concentrated on Saudi Arabia. Our paper contributes to the literature and sheds light on introducing the derivatives market in Saudi Arabia. This survey is useful to policymakers and investors as well.